Effect of Limestone Powder on Thaumasite Form of Sulfate Attack (TSA) of Cement-Based Materials - Yuxin Gao; Yaoling Luo; Lili Jia; Wen Yang; Chong Wang (Advances in Civil Engineering)
Limestone powder can cause the thaumasite form of sulfate attack (TSA) of cement-based materials, but the relationship between the content of limestone powder and the degree of TSA is unclear. Hence, six different contents of limestone powder (0%, 5%, 10%, 15%, 30%, and 45%) were used to study the effect of the limestone powder content on the TSA of cement-based materials according to appearance and Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy, X-ray diffraction (XRD), and chemical analyses. The test results indicated that limestone powder could promote sulfate attack. The formation of ettringite and gypsum was accelerated when the content of the limestone powder was not more than 10%. The degradation degree of the TSA was the most severe when the content of limestone powder was 30%. A new product, hydrated calcium carboaluminate, was found when the content of the limestone powder was 45%, and the degradation of the TSA was also delayed.